Modified sodium bismuth titanate-barium titanate-based ceramic material as well as preparation method and application thereof
By introducing BaTiO3-La(Mg2/5Al2/5Ta1/5)O3 in sodium bismuth titanate-barium titanate-based ceramics, the high entropy effect and solid phase reaction method are used to improve the impact of sodium bismuth titanate-based energy storage ceramics. The penetration strength and energy storage density solve the problems of low breakdown strength and energy storage efficiency of existing ceramic materials, and meet the needs of miniaturization of electronic products.
Patent Information
- Application Number
- CN202411267600.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing doped modified sodium bismuth titanate-based energy storage ceramics have low breakdown strength and energy storage efficiency, making it difficult to meet the needs of miniaturization of electronic products.
By introducing BaTiO3-La(Mg2/5Al2/5Ta1/5)O3 into a sodium bismuth titanate-barium titanate-based ceramic material, (1-x)(Na0.5Bi0 is formed using high entropy effect and solid phase reaction method. 5) The energy storage ceramic of 1-yBayTiO3-xLa(Mg2/5Al2/5Ta1/5)O3 increases the confusion of the material, hinders the emergence of ferroelectric macrodomains, thereby improving breakdown strength and energy storage density.
The high breakdown strength (255kV/cm) and high energy storage density (5.1J/cm3) of ceramic materials are achieved, and the temperature stability and dielectric performance of the material are improved.
Smart Images

Figure CN119118659A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage materials, and in particular relates to a modified sodium bismuth titanate-barium titanate-based ceramic material and a preparation method and application thereof. Background Art
[0002] Dielectric materials are the key core materials for manufacturing capacitors. They have the function of storing charge and are widely used in electronic circuits to realize coupling, filtering, decoupling, high-frequency vibration elimination, resonance, bypass, neutralization, timing, integration, differentiation, compensation, bootstrap, frequency division and other functions. The performance of dielectric materials directly determines the quality of capacitor components. With the development trend of miniaturization and high integration of electronic products, capacitors are facing the technical challenges of ultra-miniaturization, ultra-large capacity and ultra-thinness, which puts forward higher requirements on the dielectric breakdown strength, energy storage efficiency and energy storage density of dielectric materials. Ferroelectric materials have high spontaneous polarization strength, but because of the low breakdown strength and the large hysteresis of polarization strength with electric field, the energy storage density and efficiency are relatively low. Therefore, it is of great practical significance to develop ferroelectric energy storage materials with low polarization strength hysteresis and high breakdown strength.
[0003] Sodium bismuth titanate-barium titanate (Na 0.5 Bi 0.5 TiO3-BaTiO3) lead-free relaxor ferroelectric solid solution ceramics have excellent piezoelectric properties, which are manifested as high polarization intensity and large polarization hysteresis. However, Bi and Na are volatile elements. During the solid-phase sintering process to prepare ceramics, chemical defects such as vacancies are easily generated, resulting in large leakage loss and low breakdown strength, making it difficult to give full play to its advantages in the application of high spontaneous polarization intensity in capacitor energy storage materials. By adding appropriate amounts of other components to form a solid solution, the leakage loss can be reduced and the breakdown strength can be improved; for example, Chinese invention patent CN112341192B, a high energy storage density sodium bismuth titanate-based lead-free dielectric material and its preparation method, discloses the use of SrTi 0.9 (Cu 1 / 3 Nb 2 / 3 ) 0.1 O3-Bi 0.5 K 0.5 TiO3-modified sodium bismuth titanate-based energy storage ceramics have a breakdown strength of 220 kV / cm, an efficiency of 76%, and an effective energy storage density of 2.04 J / cm 3 ; CN111978082B A strontium magnesium niobate doped modified sodium bismuth titanate based energy storage ceramic material and its preparation method discloses the use of Sr (Mg 1 / 3 Nb 2 / 3 )O3-modified sodium bismuth titanate-based energy storage ceramics have a breakdown strength of 140 kV / cm, an efficiency of 52%, and an effective energy storage density of 1.59 J / cm 3CN111393161B Sodium bismuth titanate strontium titanate-based energy storage ceramic material and its preparation method discloses sodium bismuth titanate-based energy storage ceramic modified by SrTiO3-BaBi2Nb2O9, which has a breakdown strength of 250kV / cm, an efficiency of 86%, and an effective energy storage density of 3.09J / cm 3 CN111217604B has a method for preparing sodium bismuth titanate-based electronic ceramics with high energy storage density and efficiency. The method discloses the use of BaTiO3-Sr(Sc 0.5 Nb 0.5 )O3-modified sodium bismuth titanate-based energy storage ceramics have a breakdown strength of 185 kV / cm, an efficiency of 83%, and an effective energy storage density of 1.83 J / cm 3 .
[0004] However, the current doped and modified sodium bismuth titanate-based energy storage ceramics still have low penetration strength and energy storage effect, which makes it difficult to meet the needs of miniaturization of electronic products. Therefore, it is of great significance to develop energy storage ceramics with better performance. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a method for preparing a modified sodium bismuth titanate-barium titanate-based ceramic material, aiming to solve the problems raised in the above background technology.
[0006] The embodiment of the present invention is implemented as follows: a method for preparing a modified sodium bismuth titanate-barium titanate-based ceramic material comprises the following steps:
[0007] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula (1-x) (Na 0.5 Bi 0.5 ) 1-y Ba y TiO3-xLa(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture, wherein 0.001≤x≤0.20, 0.01≤y≤0.10;
[0008] (2) Mixing: adding anhydrous ethanol to the mixture, continuously ball milling, and mixing evenly to form a slurry;
[0009] (3) Drying: Dry the slurry at a constant temperature to remove ethanol and grind it to obtain a uniformly mixed powder;
[0010] (4) Solid-phase reaction: The uniformly mixed powder is placed in a mold for pressing and forming, and the formed block is placed in a solid-phase reaction furnace for heat preservation at high temperature to carry out solid-phase reaction;
[0011] (5) Ball milling: The material blocks after the solid phase reaction are crushed and ground to obtain ceramic powder, anhydrous ethanol is added to the ceramic powder, and the ball milling is continued to form a slurry;
[0012] (6) Drying: Drying the slurry at a constant temperature, removing ethanol, and grinding to obtain a uniformly mixed ceramic powder;
[0013] (7) Granulation: Screening the ceramic powder, adding the PVA solution thereto, pressing and molding, grinding and screening to obtain powder particles, placing the powder particles in a mold, pressing and molding with increased pressure to form a ceramic green body;
[0014] (8) Debinding: keeping the ceramic green body at high temperature to obtain a ceramic green body;
[0015] (9) Sintering: The ceramic blank is kept at high temperature and then sintered, and then cooled.
[0016] Preferably, in step (4), the pressure of the compression molding is 150-200 MPa and the time is 3-5 min;
[0017] The high temperature is 850-1100° C., and the insulation time is 3-5 hours.
[0018] Preferably, in step (7), during the process of adding the PVA solution and pressing the material, the pressure of the pressing is 150-200 MPa;
[0019] In the process of static pressure molding by increasing the pressure after pressing, the pressing pressure is 150-200 MPa, and the static pressure molding pressure is 200-300 MPa.
[0020] Preferably, in step (7), the mass concentration of the PVA solution is 3%.
[0021] Preferably, in step (8), the high temperature is 500° C. and the insulation time is 0.5-1 h.
[0022] Preferably, in step (9), the high temperature is 1150-1250° C., and the insulation time is 2-3 h.
[0023] Another object of an embodiment of the present invention is to provide a modified sodium bismuth titanate-barium titanate-based ceramic material, which is prepared by the above-mentioned preparation method.
[0024] Another object of the embodiment of the present invention is to use a modified sodium bismuth titanate-barium titanate-based ceramic material in the preparation of a dielectric material.
[0025] The present invention provides a method for preparing a modified sodium bismuth titanate-barium titanate-based ceramic material, which uses multiple elements to enter the same lattice position and utilizes the high entropy effect to increase the disorder of the material system and hinder the emergence of ferroelectric macrodomains, thereby enhancing the temperature stability and energy storage efficiency of the material, and having high breakdown strength and energy storage density. Specifically, BaTiO3-LaMO3 (M is a composite ion (Mg) with an average valence of 3) is added to the material. 2 / 5 Al 2 / 5 Ta 1 / 5 )Introduction of Na 0.5 Bi 0.5 TiO3 is prepared by solid phase reaction and sintering method with the chemical formula (1-x)(Na 0.5 Bi 0.5 ) 1-y Ba y TiO3-xLa(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 energy storage ceramics, wherein x and y represent molar fractions, the range of x is 0.001-0.20, the range of y is 0.01-0.10, Ba and La elements enter the A position of the perovskite structure to compensate for the metal ion vacancies caused by the volatilization of Bi and Na, and the composite ion M enters the B position to replace Ti, thereby enhancing the random electric field of the B position of the perovskite structure, improving the breakdown strength of the ceramic material, reducing the hysteresis characteristics of the hysteresis loop, and improving the temperature stability of the dielectric constant and the energy storage efficiency;
[0026] (1-x)(Na 0.5 Bi 0.5 ) 1-y Ba y TiO3-xLa(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 ) can reach a breakdown strength of 255kV / cm and an effective energy storage density of 5.1J / cm 3 , the energy storage efficiency reaches 92%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM photo of the ceramic sheet sample provided in Example 1 of the present invention;
[0028] Figure 2 The XRD pattern of the ceramic sheet sample provided in Example 1 of the present invention;
[0029] Figure 3 The dielectric constant and dielectric loss curves of the ceramic sheet sample provided in Example 1 of the present invention as a function of temperature;
[0030] Figure 4The hysteresis loop and energy storage property curve of the ceramic sheet sample provided in Example 1 of the present invention;
[0031] Figure 5 This is a SEM photo of the ceramic sheet sample provided in Example 2 of the present invention;
[0032] Figure 6 The XRD pattern of the ceramic sheet sample provided in Example 2 of the present invention;
[0033] Figure 7 The dielectric constant and dielectric loss curves of the ceramic sheet sample provided in Example 2 of the present invention as a function of temperature;
[0034] Figure 8 The hysteresis loop and energy storage property curve of the ceramic sheet sample provided in Example 2 of the present invention;
[0035] Fig. 9 This is a SEM photo of the ceramic sheet sample provided in Example 3 of the present invention;
[0036] Fig.10 The XRD pattern of the ceramic sheet sample provided in Example 3 of the present invention;
[0037] Fig.11 The dielectric constant and dielectric loss curves of the ceramic sheet sample provided in Example 3 of the present invention as a function of temperature;
[0038] Fig.12 The hysteresis loop and energy storage property curve of the ceramic sheet sample provided in Example 3 of the present invention;
[0039] Fig.13 This is a SEM photo of the ceramic sheet sample provided in Example 4 of the present invention;
[0040] Fig.14 The XRD pattern of the ceramic sheet sample provided in Example 4 of the present invention;
[0041] Fig.15 The dielectric constant and dielectric loss curves of the ceramic sheet sample provided in Example 4 of the present invention as a function of temperature;
[0042] Fig.16 The hysteresis loop and energy storage property curve of the ceramic sheet sample provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0044] A modified sodium bismuth titanate-barium titanate-based ceramic material, the preparation method of which comprises the following steps:
[0045] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula (1-x) (Na 0.5 Bi 0.5 ) 1-y Ba y TiO3-xLa(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture, wherein the range of x is 0.001 to 0.20, and the range of y is 0.01 to 0.10;
[0046] (2) Mixing: Add 0.5 to 2 times the mass of anhydrous ethanol to the mixture, continue ball milling for 1 hour, and mix well to form a slurry;
[0047] (3) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed powder;
[0048] (4) Solid phase reaction: the uniformly mixed powder is placed in a mold and pressed at 150-200 MPa for 3-5 minutes, and the formed block is placed in a solid phase reaction furnace and kept at 850-1100°C for 3-5 hours to cause solid phase reaction;
[0049] (5) Ball milling: The solid-phase reaction block is crushed and ground in a mortar to obtain a ceramic powder, and 0.5 to 2 times the mass of anhydrous ethanol is added to the obtained ceramic powder. The ball milling is continued for 6 to 8 hours to mix the powders evenly to form a slurry;
[0050] (6) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed ceramic powder;
[0051] (7) Granulation: The ceramic powder is sieved through a 150-mesh sieve, and then a 3% PVA solution is added thereto, and the mixture is molded at 150-200 MPa. After grinding, the mixture is sieved through a 150-mesh sieve to ensure that the PVA is evenly mixed in the ceramic powder. The powder particles are then placed in a mold, and pressed at a pressure of 150-200 MPa, and then isostatically pressed at 200-300 MPa to form a ceramic green body.
[0052] (8) debinding: keeping the ceramic green body at 500° C. for 0.5 to 1 hour to discharge the PVA in the ceramic green body to obtain a ceramic green body;
[0053] (9) Sintering: The ceramic blank is sintered at 1150-1250° C. for 2-3 hours, and after cooling, a high-entropy ion-modified sodium bismuth titanate-barium titanate-based energy storage ceramic sheet is obtained.
[0054] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0055] Example 1, chemical composition 0.98 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.02La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 energy storage ceramic, and its preparation method comprises the following steps:
[0056] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.02La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture.
[0057] (2) Mixing: Add 0.5 to 2 times the mass of anhydrous ethanol to the mixture and continue ball milling for 1 hour to mix the powders evenly to form a slurry;
[0058] (3) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed powder;
[0059] (4) Solid phase reaction: the uniformly mixed powder is placed in a mold and pressed at 150-200 MPa for 3-5 minutes, and the formed block is placed in a solid phase reaction furnace and kept at 850-1100°C for 3-5 hours to cause solid phase reaction;
[0060] (5) Ball milling: The solid-phase reaction block is crushed and ground in a mortar to obtain a ceramic powder, and 0.5 to 2 times the mass of anhydrous ethanol is added to the obtained ceramic powder. The ball milling is continued for 6 to 8 hours to mix the powders evenly to form a slurry;
[0061] (6) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed ceramic powder.
[0062] (7) Granulation: The ceramic powder is sieved through a 150-mesh sieve, and then a 3% PVA solution is added thereto, and the mixture is molded at 150-200 MPa. After grinding, the mixture is sieved through a 150-mesh sieve to ensure that the PVA is evenly mixed in the ceramic powder. The powder particles are placed in a mold, and are pressed at a pressure of 150-200 MPa, and then isostatically pressed at 200-300 MPa to form a ceramic green body.
[0063] (8) Debinding: Keep the temperature at 500°C for 0.5 to 1 hour to discharge the PVA in the ceramic green body to obtain a ceramic green body;
[0064] (9) Sintering: The ceramic blank is sintered at 1150-1250° C. for 2-3 hours, and after cooling, a high-entropy ion-modified sodium bismuth titanate-barium titanate-based energy storage ceramic sheet is obtained.
[0065] Performance Testing:
[0066] The ceramic sheet sample prepared in Example 1 was analyzed using a scanning electron microscope, and the SEM photographs were as follows: Figure 1 As shown, SEM micromorphology characterization shows that the average size of ceramic grains is about 1.6μm, dense and without obvious pores;
[0067] The sample was analyzed by X-ray diffraction and the XRD pattern was obtained as follows: Figure 2 As shown, XRD structural characterization shows that Ba 2+ ions and La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 enters the perovskite lattice to form a single stable perovskite structure solid solution ceramic phase;
[0068] The dielectric constant and dielectric loss curves of the samples with temperature are shown in Figure 3 The hysteresis loop and energy storage properties are shown in Figure 4 shown.
[0069] Example 2, chemical composition 0.94 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.06La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 energy storage ceramic, and its preparation method comprises the following steps:
[0070] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula 0.94 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06TiO3-0.06La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture;
[0071] (2) Mixing: Add 0.5 to 2 times the mass of anhydrous ethanol to the mixture and continue ball milling for 1 hour to mix the powders evenly to form a slurry;
[0072] (3) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed powder;
[0073] (4) Solid phase reaction: the uniformly mixed powder is placed in a mold and pressed at 150-200 MPa for 3-5 minutes, and the formed block is placed in a solid phase reaction furnace and kept at 850-1100°C for 3-5 hours to cause solid phase reaction;
[0074] (5) Ball milling: The solid-phase reaction block is crushed and ground in a mortar to obtain a ceramic powder, and 0.5 to 2 times the mass of anhydrous ethanol is added to the obtained ceramic powder. The ball milling is continued for 6 to 8 hours to mix the powders evenly to form a slurry;
[0075] (6) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed ceramic powder;
[0076] (7) Granulation: The ceramic powder is sieved through a 150-mesh sieve, and then a 3% PVA solution is added thereto, and the mixture is molded at 150-200 MPa. After grinding, the mixture is sieved through a 150-mesh sieve to ensure that the PVA is evenly mixed in the ceramic powder. The powder particles are placed in a mold, and are pressed at a pressure of 150-200 MPa, and then isostatically pressed at 200-300 MPa to form a ceramic green body.
[0077] (8) Debinding: Keep the temperature at 500°C for 0.5 to 1 hour to discharge the PVA in the ceramic green body to obtain a ceramic green body;
[0078] (9) Sintering: The ceramic blank is sintered at 1150-1250° C. for 2-3 hours, and after cooling, a high-entropy ion-modified sodium bismuth titanate-barium titanate-based energy storage ceramic sheet is obtained.
[0079] Performance Testing:
[0080] The ceramic sheet sample prepared in Example 2 was analyzed using a scanning electron microscope, and the SEM photographs were as follows: Figure 5 As shown;
[0081] The sample was analyzed by X-ray diffraction and the XRD pattern was obtained as follows: Figure 6 As shown;
[0082] The dielectric constant and dielectric loss curves of the samples with temperature are shown in Figure 7 The hysteresis loop and energy storage properties are shown in Figure 8 shown.
[0083] Example 3, chemical composition 0.90 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.10La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 energy storage ceramic, and its preparation method comprises the following steps:
[0084] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula 0.90 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.10La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture;
[0085] (2) Mixing: Add 0.5 to 2 times the mass of anhydrous ethanol to the mixture and continue ball milling for 1 hour to mix the powders evenly to form a slurry;
[0086] (3) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed powder;
[0087] (4) Solid phase reaction: the uniformly mixed powder is placed in a mold and pressed at 150-200 MPa for 3-5 minutes, and the formed block is placed in a solid phase reaction furnace and kept at 850-1100°C for 3-5 hours to cause solid phase reaction;
[0088] (5) Ball milling: The solid-phase reaction block is crushed and ground in a mortar to obtain a ceramic powder, and 0.5 to 2 times the mass of anhydrous ethanol is added to the obtained ceramic powder. The ball milling is continued for 6 to 8 hours to mix the powders evenly to form a slurry;
[0089] (6) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed ceramic powder;
[0090] (7) Granulation: The ceramic powder is sieved through a 150-mesh sieve, and then a 3% PVA solution is added thereto, and the mixture is molded at 150-200 MPa. After grinding, the mixture is sieved through a 150-mesh sieve to ensure that the PVA is evenly mixed in the ceramic powder. The powder particles are placed in a mold, and are pressed at a pressure of 150-200 MPa, and then isostatically pressed at 200-300 MPa to form a ceramic green body.
[0091] (8) Debinding: Keep the temperature at 500°C for 0.5 to 1 hour to discharge the PVA in the ceramic green body to obtain a ceramic green body;
[0092] (9) Sintering: The ceramic blank is sintered at 1150-1250° C. for 2-3 hours, and after cooling, a high-entropy ion-modified sodium bismuth titanate-barium titanate-based energy storage ceramic sheet is obtained.
[0093] Performance Testing:
[0094] The ceramic sheet sample prepared in Example 3 was analyzed using a scanning electron microscope, and the SEM photographs were as follows: Fig. 9 As shown;
[0095] The sample was analyzed by X-ray diffraction and the XRD pattern was obtained as follows: Fig.10 As shown;
[0096] The dielectric constant and dielectric loss curves of the samples with temperature are shown in Fig.11 The hysteresis loop and energy storage properties are shown in Fig.12 shown.
[0097] Example 4, chemical composition 0.86 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.14La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 energy storage ceramic, and its preparation method comprises the following steps:
[0098] (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula 0.86 (Na 0.5 Bi 0.5 ) 0.94 Ba 0.06 TiO3-0.14La(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture;
[0099] (2) Mixing: Add 0.5 to 2 times the mass of anhydrous ethanol to the mixture and continue ball milling for 1 hour to mix the powders evenly to form a slurry;
[0100] (3) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed powder;
[0101] (4) Solid phase reaction: the uniformly mixed powder is placed in a mold and pressed at 150-200 MPa for 3-5 minutes, and the formed block is placed in a solid phase reaction furnace and kept at 850-1100°C for 3-5 hours to cause solid phase reaction;
[0102] (5) Ball milling: The solid-phase reaction block is crushed and ground in a mortar to obtain a ceramic powder, and 0.5 to 2 times the mass of anhydrous ethanol is added to the obtained ceramic powder. The ball milling is continued for 6 to 8 hours to mix the powders evenly to form a slurry;
[0103] (6) Drying: The slurry is placed in an oven at 80°C to dry at a constant temperature to remove ethanol, and then ground with a mortar to obtain a uniformly mixed ceramic powder;
[0104] (7) Granulation: The ceramic powder is sieved through a 150-mesh sieve, and then a 3% PVA solution is added thereto, and the mixture is molded at 150-200 MPa. After grinding, the mixture is sieved through a 150-mesh sieve to ensure that the PVA is evenly mixed in the ceramic powder. The powder particles are placed in a mold, and are pressed at a pressure of 150-200 MPa, and then isostatically pressed at 200-300 MPa to form a ceramic green body.
[0105] (8) Debinding: Keep the temperature at 500°C for 0.5 to 1 hour to discharge the PVA in the ceramic green body to obtain a ceramic green body;
[0106] (9) Sintering: The ceramic blank is sintered at 1150-1250° C. for 2-3 hours, and after cooling, a high-entropy ion-modified sodium bismuth titanate-barium titanate-based energy storage ceramic sheet is obtained.
[0107] Performance Testing:
[0108] The ceramic sheet sample prepared in Example 4 was analyzed using a scanning electron microscope, and the SEM photographs were as follows: Fig.13 As shown;
[0109] The sample was analyzed by X-ray diffraction and the XRD pattern was obtained as follows: Fig.14 As shown;
[0110] The dielectric constant and dielectric loss curves of the samples with temperature are shown in Fig.15 The hysteresis loop and energy storage properties are shown in Fig.16 shown.
[0111] In summary, the ceramic material prepared by the embodiment of the present invention has a breakdown strength of up to 255 kV / cm and an effective energy storage density of 5.1 J / cm 3 , the energy storage efficiency reaches 92%.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified sodium bismuth titanate-barium titanate-based ceramic material, characterized in that: The following steps are involved: (1) Ingredients: Sodium carbonate, bismuth oxide, titanium oxide, barium carbonate, lanthanum oxide, magnesium oxide, aluminum oxide and tantalum oxide are mixed according to the chemical formula (1-x) (Na 0.5 Bi 0.5 ) 1-y Ba y TiO3-xLa(Mg 2 / 5 Al 2 / 5 Ta 1 / 5 )O3 in a molar ratio to obtain a mixture, wherein 0.001≤x≤0.20, 0.01≤y≤0.10; (2) Mixing: adding anhydrous ethanol to the mixture, continuously ball milling, and mixing evenly to form a slurry; (3) Drying: Dry the slurry at a constant temperature to remove ethanol and grind it to obtain a uniformly mixed powder; (4) Solid-phase reaction: The uniformly mixed powder is placed in a mold for pressing and forming, and the formed block is placed in a solid-phase reaction furnace for heat preservation at high temperature to carry out solid-phase reaction; (5) Ball milling: The material blocks after the solid phase reaction are crushed and ground to obtain ceramic powder, anhydrous ethanol is added to the ceramic powder, and the ball milling is continued to form a slurry; (6) Drying: Drying the slurry at a constant temperature, removing ethanol, and grinding to obtain a uniformly mixed ceramic powder; (7) Granulation: Screening the ceramic powder, adding the PVA solution thereto, pressing and molding, grinding and screening to obtain powder particles, placing the powder particles in a mold, pressing and molding with increased pressure to form a ceramic green body; (8) Debinding: keeping the ceramic green body at high temperature to obtain a ceramic green body; (9) Sintering: The ceramic blank is kept at high temperature and then sintered, and then cooled.
2. The method for preparing the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 1, characterized in that: In step (4), the compression molding pressure is 150-200 MPa and the time is 3-5 min; The high temperature is 850-1100° C., and the insulation time is 3-5 hours.
3. The method for preparing the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 1, characterized in that: In step (7), the PVA solution is added thereto, and during the pressing process, the pressing pressure is 150-200 MPa; In the process of static pressure molding by increasing the pressure after pressing, the pressing pressure is 150-200 MPa, and the static pressure molding pressure is 200-300 MPa.
4. The method for preparing the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 1, characterized in that: In step (7), the mass concentration of the PVA solution is 3%.
5. The method for preparing the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 1, characterized in that: In step (8), the high temperature is 500° C. and the insulation time is 0.5-1 h.
6. The method for preparing the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 1, characterized in that: In step (9), the high temperature is 1150-1250° C. and the insulation time is 2-3 hours.
7. A modified sodium bismuth titanate-barium titanate-based ceramic material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the modified sodium bismuth titanate-barium titanate-based ceramic material according to claim 7 in the preparation of dielectric materials.
Citation Information
Patent Citations
Composite ion modified sodium bismuth titanate-based energy storage ceramic material and preparation method thereof
CN117024141A
Potassium-sodium niobate-based ceramic material with high energy storage under low electric field and preparation method of potassium-sodium niobate-based ceramic material
CN117285353A
Bismuth sodium titanate-barium zirconium titanate base lead-free piezoelectric ceramic and its producing method
JP2007031219A
Lead-free piezoelectric ceramic composition with excellent electric field-induced strain property and preparation method of the same
KR1020170107410A
